Diagnosis and treatment of acute isolated proximal internal carotid artery occlusions: a narrative review. (November 2022) - Kargiotis, Odysseas; Psychogios, Klearchos; Safouris, Apostolos; Spiliopoulos, Stavros; Karapanayiotides, Theodore; Bakola, Eleni; Mantatzis, Michail; Dardiotis, Efthimios; Ellul, John; Giannopoulos, Sotirios; Magoufis, Georgios; Tsivgoulis, Georgios
The clinical manifestations of proximal (extracranial) internal carotid artery occlusions (pICAOs) may range from asymptomatic to acute, large, and devastating ischemic strokes. The etiology and pathophysiology of the occlusion, intracranial collateral status and patient's premorbid status are among the factors determining the clinical presentation and outcome of pICAOs. Rapid and accurate diagnosis is crucial and may be assisted by the combination of carotid and transcranial duplex sonography, or a computed tomography/magnetic resonance angiography (CTA/MRA). It should be noted that with either imaging modalities, the discrimination of a pseudo-occlusion of the extracranial internal carotid artery (ICA) from a true pICAO may not be straightforward. In the absence of randomized data, the management of acute, symptomatic pICAOs remains individualized and relies largely on expert opinion. Administration of intravenous thrombolysis is reasonable and probably beneficial in the settings of acute ischemic stroke with early presentation. Unfortunately, rates of recanalization are rather low and acute interventional reperfusion therapies emerge as a potentially powerful therapeutic option for patients with persistent and severe symptoms. However, none of the pivotal clinical trials on mechanical thrombectomy for acute ischemic stroke randomized patients with isolated extracranial large vessel occlusions. On the contrary, several lines of evidence from non-randomized studies have shown that acute carotid endarterectomy, or endovascular thrombectomy/stenting of the ICA are feasible and safe, and pοtentially beneficial. The heterogeneity in the pathophysiology and clinical presentation of acute pICAOs renders patient selection for an acute interventional treatment a complicated decision-making process. The present narrative review will outline the pathophysiology, clinical presentation, diagnostic challenges, and possible treatment options for pICAOs.